2012
DOI: 10.1021/ja3060436
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Cyclopropenes As Bioorthogonal Chemical Reporters

Abstract: Chemical reporters are unique functional groups that can be used to label biomolecules in living systems. Only a handful of broadly applicable reporters have been identified to date, owing to the rigorous demands placed on these functional groups in biological settings. We describe here a new chemical reporter-cyclopropene-that can be used to target biomolecules in vitro and in live cells. A variety of substituted cyclopropene scaffolds were synthesized and found to be stable in aqueous solution and in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
345
0
10

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(366 citation statements)
references
References 51 publications
3
345
0
10
Order By: Relevance
“…Furthermore, terminal alkynes, which are highly reactive in CuAAC reactions, only react with tetrazines, unless electron-donating substituents are present or relatively harsh reaction conditions are applied. The combination of iEDDA dienophiles (TCO 43 and methylcyclopropene, 44 respectively) and dibenzocyclooctyne as the SPAAC acceptor finally allowed a copper-free, mutually orthogonal and bioorthogonal protocol. DFT (density functional theory) calculations revealed that the introduction of the two fused benzene rings in dibenzocyclooctyne derivatives raised the distortion energy necessary to attain the first transition state TS in iEDDA reactions, 18 so that the reaction rate for tetrazines and dibenzocyclooctyne was drastically reduced.…”
Section: Mutual Orthogonality With Other Click Reactionsmentioning
confidence: 99%
“…Furthermore, terminal alkynes, which are highly reactive in CuAAC reactions, only react with tetrazines, unless electron-donating substituents are present or relatively harsh reaction conditions are applied. The combination of iEDDA dienophiles (TCO 43 and methylcyclopropene, 44 respectively) and dibenzocyclooctyne as the SPAAC acceptor finally allowed a copper-free, mutually orthogonal and bioorthogonal protocol. DFT (density functional theory) calculations revealed that the introduction of the two fused benzene rings in dibenzocyclooctyne derivatives raised the distortion energy necessary to attain the first transition state TS in iEDDA reactions, 18 so that the reaction rate for tetrazines and dibenzocyclooctyne was drastically reduced.…”
Section: Mutual Orthogonality With Other Click Reactionsmentioning
confidence: 99%
“…[6] Fort his alkene,t he (Z)-isomer of 5 showed alower rate constant than (E)-5.Introduction of an electrondonating substituent on the phenyl ring of 8 increased the rate constant further to 27 m À1 s À1 . To evaluate the effect of the boronic acid on the alkenes reactivity,wecompared the rate constants of the fastest VBAs (E)-5 and 8 to the alkene derivatives lacking the boronic acid (Table 1, Entries 4a nd 5).…”
mentioning
confidence: 97%
“…Importantly, CpK was shown to direct site-specific modification of green fluorescent protein inside HEK293T cells via the tetrazole-based photoclick chemistry. Notably, the cyclopropene moiety has also been used as a reaction partner in tetrazine ligation [53,54], with its reactivity preference between the tetrazine and tetrazole chemistries depending on the substitution pattern [55]. Realizing the cyclopropene reactivity can be further increased by reducing the steric hindrance at position 3, we fused a cyclobutane ring with the cyclopropene to generate spiro[2.3]hex-1-ene (Sph) [56].…”
Section: Site-specific Labeling Of Proteins Via the Photoinduced Tetrmentioning
confidence: 99%